DETERMINATION OF THE PRESENCE OF Ornithonussus spp. IN BREEDER HENS AND ROOSTERS IN THREE GENETIC LINES ON A FARM IN SOLANO COUNTY, CALIFORNIA, USA - Cangalaya Villanueva, Alessandra; Casas Astos, Eva; Cerro Temoche, Luis (Revista de Patologia Tropical / Journal of Tropical Pathology, 2020)
Acarosis in birds may cause irritation, stress, reduction of food intake and, consequently, reduction in egg production and quality. In this sense, the Ornithonyssus sylviarum mite is considered one of the most aggressive mites to bird health due to its permanent behavior. The objective of this work is to determine the presence of Ornithonyssus spp. in three genetic lines of pedigree breeding chickens and roosters on a farm in the state of California, USA, and identify the species of Ornithonyssus spp. present in the three genetic lines studied. A sampling of 103 pedigree chickens and roosters was carried out to determine the presence of Ornithonyssus spp. The samples were collected from the feathers under the cloaca, preserved in 70% alcohol, then rinsed with 10% sodium hydroxide and evaluated, by direct observation through the microscope and stereoscope, in order to visualize and identify their morphological characteristics. The results show the presence of Ornithonyssus spp. in 99.0% (102/103) of the birds, identifying an average of 135, 121 and 30 mites per bird according to lines A, B and C, respectively. The species identified were Ornithonyssus sylviarum, Ornithonyssus bursa and Ornithonyssus bacoti in 89.8%, 1.4% and 0.8% respectively, with 8.1% Ornithonyssus spp. In conclusion, Ornithonyssus spp. was present in the pedigree breeding chickens and roosters in the three genetic lines. Ornithonyssus sylviarum was the predominant species.